Goal-based organizational modeling oriented towards late requirements generation using the Tropos Framework - Estrada, Hugo; Castro, Jaelson F. B.; Pastor, Oscar; Martínez, Alicia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2003: Anais do XVII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2003.23858, 2003)
Recently, a lot of research efforts in software engineering have focused on integrating organizational modeling as a key piece in requirements engineering. In these research works, the business models are proposed as the source of the software requirements specification process. However, the majority of these works focus only on the definition of notations that permit the representation of the semantics of the organizational context, and only a few works define processes that use these notations in a methodological way. This lack of a methodological process for generating organizational models makes practical application in software development enterprises difficult. The objective of this paper is to present a goal-based method to generate organizational models represented in the Tropos framework. These models are later used as starting point of the requirements specification process of the information system. This will enable us to develop information systems that integrate the necessary functionality so that the organizational actors perform their tasks and fulfill their goals.